Heliotherapy and Walking Therapy to Reduce Glukosa Levels in Type 2 Diabetes Milletus (T2DM): A Comparative Study - Mahmud, Mulyani Hertikawati; Widyawati, Ika Yuni; Wahyudi, Andri Setiya (Indonesian Journal of Global Health Research, 2024)
Diabetes Mellitus is a chronic disease that has bad complications for the sufferer's health, so it requires non-pharmacological treatment. The aim of this study is to explain the effectiveness of non-pharmacological therapies such as heliotherapy and walking therapy in reducing random glucose levels (RBS) in patients with type 2 diabetes mellitus (DM). This study used a Pre-Post Test With Two Group Design research design. The population for this study consisted of 32 respondents, divided into two groups: the heliotherapy intervention group and the walking intervention group, each with 16 respondents. The research subjects were selected based on the criteria for diabetes mellitus patients. The independent variables were heliotherapy and walking therapy, while the dependent variable was the reduction in RBS levels. Research instruments included heliotherapy standard operating procedures (SOP), walking therapy SOP, Glucometer, and observation sheets. Data analysis was performed using paired t-tests and independent t-tests. The statistical test results showed a p-value of 0.353 (α>0.05), indicating that there is no significant difference in effectiveness between heliotherapy and walking therapy in reducing RBS levels in patients with type 2 diabetes mellitus (DM). It can be concluded that the reduction in RBS levels is higher with walking therapy compared to heliotherapy in patients with type 2 DM.